2023
DOI: 10.1002/cam4.6405
|View full text |Cite
|
Sign up to set email alerts
|

Association of PD‐L1 tumor proportion score ≥20% with early resistance to osimertinib in patients with EGFR‐mutated NSCLC

Yusuke Hamakawa,
Yoko Agemi,
Aya Shiba
et al.

Abstract: BackgroundThe relationship between epidermal growth factor receptor tyrosine kinase inhibitor (EGFR‐TKI) resistance, including osimertinib, and programmed cell death‐ligand 1 (PD‐L1) expression status in EGFR‐mutated non‐small cell lung carcinoma (NSCLC) remains unclear.Patients and MethodsWe retrospectively analyzed 64 patients with unresectable advanced or metastatic NSCLC carrying EGFR exon 19 deletions (ex19del) or EGFR exon 21 L858R substitutions (L858R) who received osimertinib as the first‐line treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The prognostic signi cance of PD-L1 expression in EGFR-mutated NSCLC patients, particularly regarding PFS with TKI, remains an area of ongoing research. Most studies (10,11,16,17,18,19) and meta-analyses (8) have shown that patients with positive or high PD-L1 expression generally have poorer outcomes. This aligns with our ndings, which bodes ill for this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic signi cance of PD-L1 expression in EGFR-mutated NSCLC patients, particularly regarding PFS with TKI, remains an area of ongoing research. Most studies (10,11,16,17,18,19) and meta-analyses (8) have shown that patients with positive or high PD-L1 expression generally have poorer outcomes. This aligns with our ndings, which bodes ill for this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…While a majority of previous studies have designated 50% as the threshold to differentiate between high and low PD-L1 expression (9, 16), there is growing evidence of prognostic variances between PD-L1 positivity and negativity (17,29,30,31). A recent study has proposed that a 20% cut-off point might more accurately re ect these prognostic differences (10). This suggestion is particularly relevant in light of the substantial variability in PD-L1 expression detection caused by different antibodies and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation